Teacher and actor perceptions of a recent journey involving clinical simulation - Ana Cláudia Carneiro; Iêda Aleluia; Marília Fagundes; Maristela Sestelo; Regina Brasil; Tânia Soares (Escola Bahiana de Medicina e Saúde Pública, 2021)
INTRODUCTION: Medical education is under many modifications, insertions and new perspectives on the learning teaching process, and the realistic simulation is one of these changes. It includes technical skills, but also attitudinal skills. The original idea of simulation is to integrate theoretical knowledge, skills and attitude.  OBJECTIVES: to tell the experience of building a simulation core in our institution, with faculty development and culture changes. METHODS: using the cartography, 04 teachers and 02 female actors told their narratives by memories and reflections about the path travelled and the knowledge built. RESULTS AND DISCUSSION: each one experience on the first simulation scenario in 2018.2. We reached the original objective (students' participation and study), but also the depth of each one experience and reflection. There was a balance between technique and sensibility. The actor's role to build and concretize the project was essential in this balance. CONCLUSIONS: the simulation strengthened the attitudinal competences, promoted the faculty development and showed the importance to put together art and technique on the health professional training.